2003
DOI: 10.1038/sj.bmt.1703787
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of peripheral blood progenitor cells with vinorelbine and granulocyte colony-stimulating factor in multiple myeloma patients is reliable and cost effective

Abstract: Summary:Cyclophosphamide with granulocyte colony stimulating factor (G-CSF) is commonly used to mobilize stem cells in multiple myeloma. Timing of collection is variable and incidence and severity of side effects is substantial. To optimize timing of collection, to reduce side effects and to limit costs of the procedure, we evaluated vinorelbine, a drug shown to have activity in multiple myeloma, in combination with G-CSF as mobilizing regimen. A total of 19 consecutive patients with advanced stage multiple my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…43,44 After chemomobilization, the lapse of time before the number of CD34 þ cells peaks varies substantially between patients. 25,43,44 WBC counts and CD34 þ cell counts must be monitored over the course of several days to determine when to begin apheresis. 44 Algorithms intended to reduce the incidence of unanticipated PBSC collections and to streamline care by predicting the timing of apheresis after chemomobilization have been used with limited success.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 After chemomobilization, the lapse of time before the number of CD34 þ cells peaks varies substantially between patients. 25,43,44 WBC counts and CD34 þ cell counts must be monitored over the course of several days to determine when to begin apheresis. 44 Algorithms intended to reduce the incidence of unanticipated PBSC collections and to streamline care by predicting the timing of apheresis after chemomobilization have been used with limited success.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
“…25,43,44 WBC counts and CD34 þ cell counts must be monitored over the course of several days to determine when to begin apheresis. 44 Algorithms intended to reduce the incidence of unanticipated PBSC collections and to streamline care by predicting the timing of apheresis after chemomobilization have been used with limited success. 39 Hence, patients who undergo mobilization with chemotherapy plus cytokines often require unscheduled apheresis sessions on weekends, a practice that necessitates inefficient allocation of hospital resources and staff.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…We may therefore speculate that this provided us with more consistent results compared with those studies reported previously using different doses, regimens and timing of rhG-CSF. [16][17][18][19][20][21][23][24][25] We concluded that PBSC mobilization after the 'late' use of rhG-CSF is an effective approach, and that in routine clinical practice the late use of rhG-CSF may therefore be used for PBSC collections after chemotherapy-based mobilization regimens in this cost-conscious era.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that in most of these studies, the primary objective was not to evaluate 'late' administration of rhG-CSF. [16][17][18][19][20][21] These studies have evaluated the 'late' use of rhG-CSF (4 days after chemotherapy), at varied doses and schedules with comparable results with those obtained after starting rhG-CSF immediately after chemotherapy. 18,19,21 Mollee et al 16 compared CY þ rhG-CSF with CE þ rhG-CSF of 10 mg/kg once daily for PBSC mobilization in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%